Pengaruh Return On Asset, Capital Adequacy Ratio, Dana Pihak Ketiga Dan Non-Performing Financing Terhadap Market Share Perbankan Syariah - Retno Puji Astuti (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this study was to analyze the effect of return on assets, CAR, third-party funds, and non-performing financing on Islamic banking market share. The population of this study is Islamic banking registered with the Financial Services Authority (OJK) for the period 2017–2022. The sampling method used was purposive sampling, with a total sample of 10 Islamic commercial banks. The data analysis technique used in this research is multivariate regression analysis using Eviews 10 statistical tools. The results of this study indicate that ROA and DPK affect the market share of Islamic banking. CAR and NPF do not affect on the market share of Islamic banking